Teaching Technologies: Continuous Interplay Between Educational and Industrial Advances - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Teacher Education in the Wake of Covid-19)
The field of teaching technologies is in constant interplay between educational and industrial advances. Since the beginning of the twenty-first century, digitalization and automatization have become increasingly important. In industrial and social life, we see similar fast-moving developments. These factors challenge education, specifically vocational education, greatly, and raise two very different, yet very much connected questions: how to prepare students for their vocational lives and how to prepare teachers to communicate the necessary competencies to their students? This chapter provides an overview of advances, challenges, and possible solutions, focusing on the three key fields of vocational education in Germany: Industry 4.0, Education 4.0, and innovative teacher education. Most importantly, however, the text examines the continuous interplay between and among these fields. The beginning of the chapter is dedicated to vocational teacher education, in accordance with industrial and educational advances. Specifying this, characteristics of Industry 4.0, as well as students' and teachers' perceptions of Industry 4.0, are discussed. This is followed by an introduction to the concept of so-called learning factories as a possible way of integrating aspects of Industry 4.0 in German vocational schools. The end of the chapter is dedicated to the required changes in educational settings today and in the future. Though Industry 4.0, Education 4.0, and innovative teacher education are each widely discussed in the current literature, the interplay of all three fields reveals a research gap. This chapter tries to close this gap and provide an important contribution to the research field.

Gewerblich-technische Lehrkräftebildung in Deutschland – Analyse der Einflüsse auf das akademische Selbstkonzept von Lehramtsstudierenden technischer (beruflicher) Fachrichtungen - Vernholz, Mats; Temmen, Katrin

Teacher Educators' Experiences and Expressions of Emotion During the Pandemic: International Perspectives - Newberry, Melissa; Rizvi, Meher; van der Want, Anna; Jonas-Ahrend, Gabriela; Kaldi, Stavroula; Kihara, Toshiyuki; Franco, Juan Vicente Ortiz; Ratnam, Tara (Advances in Research on Teaching)

Evaluation of Physics Textbooks - Kapanadze, Marika; Jonas-Ahrend, Gabriela; Mazzolini, Alexander; Joubran, Fadeel (The International Handbook of Physics Education Research: Special Topics)
Physics textbooks are generally viewed as important tools that provide well-presented and reliable information that supports and enhances students' understanding of critical concepts. The main goal of this chapter is to find out what attention has been given to textbook evaluation in physics education research literature. Studies about physics textbooks from different countries and different eras are discussed and analyzed, and a broad overview about aspects that influence the efficacy of physics textbooks are presented. Research papers that discuss the importance and influence of digital textbooks (and similar technological resources) are also analyzed.

Teacher Educators' Experiences and Expressions of Emotion During the Pandemic: International Perspectives - Newberry, Melissa; Rizvi, Meher; van der Want, Anna; Jonas-Ahrend, Gabriela; Kaldi, Stavroula; Kihara, Toshiyuki; Franco, Juan Vicente Ortiz; Ratnam, Tara (Advances in Research on Teaching)

Lessons learned from a global review study of physics textbook evaluation and its implications for teaching and learning in the classroom - Jonas-Ahrend, Gabriela; Fraser-Abder, Pamela; Kapanadze, Marika; Joubran, Fadeel; Mazzolini, Alexander

Physiklehrbücher im Fokus der fachdidaktischen Forschung - ein internationaler Literatur-Review - Jonas-Ahrend, Gabriela; Kapanadze, Marika; Mazzolini, Alexander; Joubran, Fadeel

Ergebnisse einer Reviewstudie zur Evaluation von Physiklehrbüchern - Jonas-Ahrend, Gabriela; Kapanadze, Marika; Mazzolini, Alexander; Joubran, Fadeel

Knowledge Transfer Concepts for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Temmen, Katrin; Bode, Henrik (2023 IEEE Global Engineering Education Conference (EDUCON))

Academic self-concepts of pre-service technology teachers for vocational education in Germany according to the TPACK- Model - Vernholz, Mats (Living and Leading in the Next Era: Connecting Teaching, Research, Citizenship and Equity)